Providing mode locking in fiber ring lasers - Гнатенко, О. С.; Мачехін, Ю. П.; Курський, Ю. С.; Обозна, В. П. (СумДУ, 2018)
In this paper, the authors proposed a new optical scheme for providing passive mode locking in a fiber ring laser. The idea is to use a liquid crystal display (LC) cells for the realization of nonlinear polarization evolution. Also, in the work theoretically investigated the dispersion of optical fibers of different types to construct fiber lasers with ring resonators. Was studying the stability of polarization to ensure nonlinear evolution polarization, by solving the Ginzburg-Landau equation, and also the control of the polarization of the radiation by the LC cell using the Oseen-Frank equation.
Keywords: Optical fiber; Laser; Liquid crystal cell; Mode locking; Dispersion; Transmittance; Polarization; Wave plates